Chefs Evaluate Syrup from the Wild Bigleaf Maple (Acer macrophyllum): A New Artisanal Food from Pacific Northwest Forests - Lisa M. L. Price; Ann Colonna; Eric T. Jones (Gastronomy)
This paper examines a new artisanal food product made from bigleaf maple trees (Acer macrophyllum). These trees are indigenous to, and thrive in, the moist and mild climate of the Pacific Northwestern regions of the United States and Canada. Small producers have a new artisanal product from this historically valuable tree. The sap is collected from family-owned woodland trees to produce maple syrup. To better understand the gastronomic potential of bigleaf maple syrup, we conducted sensory evaluations with culinary professionals. In this study undertaken in Oregon, the syrup from three small independent producers was subjected to sensory hedonic and attribute assessments by 62 chefs. The results of the sensory assessments and the details of the testing methods and analysis are presented. This paper examines the agreement among the chefs and the implications for the culinary acceptance of this new artisanal product. We discuss in detail (1) the complexity of flavor; (2) the most likely use of bigleaf maple syrup in various foods or as a sweetener; (3) and the four most important reasons for purchasing bigleaf maple syrup consisting of both environmental and taste attributes.